On the numerical solution of equilibrium problems for elastic solids with bounded tensile strength - Lucchesi, Massimiliano; Padovani, Cristina; Pasquinelli, Giuseppe (Computer methods in applied mechanics and engineering, 1995)
This paper proposes a numerical method for the solution of equilibrium problems of elastic solids with bounded tensile strength. Some boundary-value problems are solved numerically and the solution obtained is compared to the exact one. Finally, a masonry spherical dome subjected to its own weight and to a point load at the crown is studied.